Bisphenol A promotes hepatic lipid deposition involving Kupffer cells M1 polarization in male mice. Issue 2 (August 2017) - Lv, Qiong; Gao, Rufei; Peng, Chuan; Yi, Juan; Liu, Lulu; Yang, Shumin; Li, Danting; Hu, Jinbo; Luo, Ting; Mei, Mei; Song, Ying; Wu, Chaodong; et al.
Abstract : Bisphenol A (BPA), one of the most common environmental endocrine disruptors, is considered to promote hepatic lipid deposition. However, the mechanism has not been fully elucidated. The polarization of Kupffer cells (KCs) plays an important role in hepatic inflammation by promoting pro-inflammatory M1 phenotype (M1KCs), which contributes to dysregulated lipid metabolism. The purpose of this study is to investigate the role of KC polarization in BPA-induced hepatosteatosis in male mice. In this study, we examined hepatic lipid contents and quantified M1KC in BPA-treated CD1 mice, and further explored the interaction between KCs and hepatocytes using conditional HepG2 cell culture. BPA treatment significantly increased hepatic fat contents in CD1 mice, accompanied by increased number of pro-inflammatory M1KCs and enhanced secretion of inflammatory cytokines. Increased lipid contents were also observed in HepG2 cells treated with BPA. Interestingly, higher TG contents were observed in HepaG2 cells treated with conditional media from BPA-treated KCs, compared with those treated with BPA directly. Incubation of KCs with BPA promoted the polarization of KCs to pro-inflammatory M1 dominant subtypes, which was blocked by estrogen antagonist ICI182780. Taken together, our results revealed that M1KCs polarization is involved in BPA-induced hepatic fat deposition, which is possibly associated with the estrogen receptor signaling pathway.